State of the world's cities, 2012/2013 : prosperity of cities - United Nations Human Settlements Programme (New York : Routledge, 2013)
The city is the home of prosperity. It is the place where human beings find satisfaction of basic needs and access to essential public goods. The city is also where ambitions, aspirations and other material and immaterial aspects of life are realized, providing contentment and happiness. It is a locus at which the prospects of prosperity and individual and collective well-being can be increased. What this new edition of State of the world's cities shows is that prosperity for all has been compromised by a narrow focus on economic growth. UN-Habitat suggests a fresh approach to prosperity beyond the solely economic emphasis, including other vital dimensions such as quality of life, adequate infrastructures, equity and environmental sustainability. The Report proposes a new tool - the City Prosperity Index - together with a conceptual matrix, the Wheel of Prosperity, both of which are meant to assist decision makers to design clear policy interventions. The Report advocates for the need of cities to enhance the public realm, expand public goods and consolidate rights to the'commons' for all as a way to expand prosperity. This comes in response to the observed trend of enclosing or restricting these goods and commons in enclaves of prosperity, or depleting them through unsustainable use. - Publisher.
Includes bibliographical references (p. 174-180) and index.
Keywords: Cities and towns; Cities and towns -- Statistics; Globalization; Cities and towns -- Growth; Urban policy